Study of the use of subject related printed library books written in english by b.a. special degree undergraduates in library and information science for their studies - Alahakoon, P.P.; Dasanayake, D.M.A. (university of Jaffna, 2014)
The library is considered as an important figure in a university that facilitates undergraduates' individual learning and research. Yet the researchers observed a crucial factor that the majority of the undergraduates in the Department of Library and Information Science of the University of Kelaniya, Sri Lanka do not often utilize subject related printed library books in English for their studies. This study focused on the use of subject related printed library books written in nd rd English by 100 undergraduates (2 and 3 Years) who were following the Special Degree Program in Library and Information Science in the Faculty of Social Sciences. The data was collected through a questionnaire and from the reference and lending sections of the university library and they were analyzed qualitatively. According to data, the undergraduates brought forward issues such as difficulty in finding books in English with updated facts, inconsiderable service provided by the Library, little motivation given by the parents and colleagues to refer to English medium books and rd inability to understand the texts due to limited proficiency in English. Interestingly, the 3 year nd undergraduates were more interested in using library books in English than the 2 year undergraduates and more than 75% of the sample mostly used the lending section to refer to books. The study explored the methods of increasing undergraduates' utilization of subject related printed library books in English by amplifying their reading skills, language proficiency and updating the lists of bibliography including magazines, periodicals, newsletters and so on which are updated with the latest information. It further discussed the degree of success of the suggestions made by the undergraduates to use internet to search knowledge and the importance of enhancing interaction between the library and the staff in making the library more beneficial.
Keywords: Utilization of subject related printed library books in english; Library and information science; 2 and 3 years' undergraduates; Qualitative analysis